User Satisfaction Assessment of Final Project Supervisor Monitoring Information System Using User Experience Design Method - Fauzan Asrin; Yus Sholva (Journal of Information System and Informatics, 2022)
Completing the final project takes a guiding process n the final project where the concept of final project guidance itself is an effort to help students to provide direction, assistance, suggestions, and criticisms that arise from the preparation of the final project by the supervisor. However, sometimes the guidance process is not optimal. Lecturers or students themselves can cause this. The difficulty for lecturers to help students during tutoring is the limited communication time that is too narrow on campus and the difference in busy schedules between students and supervisors. Managing the time for the final independent project is also an obstacle that causes the completion of the final project to be delayed. Some students tend to be less active in carrying out guidance if the supervisor does not provide a fixed guidance schedule or does not provide a target time for students to complete the revision of the final project from the supervisor. So, it is necessary to build an information system for monitoring the final project supervisor to monitor the existence of supervisor. This study uses the User Experience Design Process to increase user satisfaction in interacting with the product. And at the final stage, a Usability Testing evaluation is carried out to test the product's usefulness. The results of this study are in the form of an assessment of how satisfied and comfortable a user is with a product, system, and service using an interface